Classification of Human Emotions from EEG Signals using Statistical Features and Neural Network - Yuen, Chai Tong; San, Woo San; Seong, Tan Ching; Rizon, Mohamed (International Journal of Integrated Engineering, 2009)
A statistical based system for human emotions classification by using electroencephalogram (EEG) is proposed in this paper. The data used in this study is acquired using EEG and the emotions are elicited from six human subjects under the effect of emotion stimuli. This paper also proposed an emotion stimulation experiment using visual stimuli. From the EEG data, a total of six statistical features are computed and back-propagation neural network is applied for the classification of human emotions. In the experiment of classifying five types of emotions: Anger, Sad, Surprise, Happy, and Neutral. As result the overall classification rate as high as 95% is achieved.